Assessment of Romanian School-Aged Children’s Lifestyle and Associated Factors: A Longitudinal Study Performed Before and During COVID-19 Pandemic - Lucia Maria Lotrean; Anda Valentina Trandafir; Florina Gabor-Harosa (Children)
Background and Objectives: The COVID-19 pandemic affected children’s lifestyle, due to strict lockdown restrictions. This study evaluated Romanian children’s lifestyle prior to and during the pandemic and their associated factors. Materials and Methods: A longitudinal study was performed in 7 urban schools from Romania. Data were gathered at baseline (T1), from October to November 2019, and follow-up (T2), from December 2020 to February 2021. Results: A total of 880 children were enrolled at baseline, 484 at T2, and 350 in both evaluations. Initially, 66.3% did not perform at least one hour of physical activity per day, two thirds did not sleep at least 9 h per night during the week, and more than one third used the internet more than 2 h daily. Investigating changes before and during COVID-19 among students participating at both evaluations, a statistically significant drop in physical activity and sleep time during the week was recorded, while weekend sleep and internet use increased. Several gender- and age-related differences were noted. Physical activity and sleep patterns as well as internet use behavior at T1 predicted the same behavior at T2. Reduced sleep during the week and internet overuse were positively associated at both waves as well as longitudinally. Conclusions: These findings highlight calls for combined strategies that include parents, schools, and community, aiming to enhance a healthier lifestyle among children.